The role of ubiquinone in the respiratory chain of Acetobacter xylinum - Benziman, Moshe (1968)
1. Whole cells of Acetobacter xylinum were found to contain a quinone of the ubiquinone (coenzyme Q) group. The quinone was isolated from the cells and crystallized. It was identified by its physical, chemical and spectroscopic properties as a ubiquinone with 10 isoprene units (ubiquinone-10). No naphthaquinone was detected in the cells. 2. Cell-free extracts prepared by means of a French pressure cell were separated into three fractions by differential centrifugation. The ubiquinone was located predominantly in the particulate fraction sedimenting at 33000g, which also contained most of the NADH oxidase and malate oxidase activities. The concentration of ubiquinone-10 in extracts was similar to that of the flavoproteins and about three times the concentration of the individual cytochromes. 3. Aerobic incubations of crude extracts with either NADH or malate resulted in reduction of the endogenous ubiquinone-10 to steady-state concentrations of 55 and 40% of the total quinone respectively. In the presence of cyanide more than 95% of the endogenous ubiquinone-10 was reduced by either NADH or malate. 4. The initial rate of reduction of endogenous ubiquinone-10 by malate and the rate of ubiquinol oxidation, in A. xylinum extracts, were found to be compatible with the overall rate of malate oxidation with oxygen. 5. The effects of various respiratory inhibitors on the oxidation–reduction reactions of the endogenous quinone indicate that its position on the respiratory chain is between the malate flavoprotein dehydrogenase and the cytochrome chain.